Gross Biometrical Analysis of the Sternum of Indigenous Poultry of Poonch Region of Jammu and Kashmir - Jasvinder Singh Sasan; Shalini Suri; Kamal Sarma (The Indian Veterinary Journal, 2026)
The present study was conducted on the sternum (N=06) of indigenous poultry of Poonch region. The sternum is the major supportive element within the ventral body wall. The body of the sternum was elongated, concave dorsally and convex ventrally for attachment to breast muscles. The cranio-lateral process was elongated and directed cranially. The caudo-lateral process started as a single process, which bifurcated into a smaller dorsal and a longer ventral process, both directed caudally. The caudo-dorsal process was much wider at its terminal end than the caudo-ventral process. Two lateral pneumatic foramina were located on either side of mid-line towards the cranial end of the body, whereas the median pneumatic foramen was absent. The cranial border of the sternum presented transversely elongated grooves separated by a rostrum to articulate with the distal extremity of the coracoid bone just below the cranial border. Anteriorly, the lateral border presented four facets for the sternal ribs. The rostrum was a quadrilateral plate-like in outline. The ventral surface presented triangular shaped keel (carina) in the midline. The cranial border was concave, and the apex was in level as the origin of the caudo-lateral process. Length of sternum was 13.36 ± 0.093 cm. The width of the sternum was maximum at the level of facets (3.27 ± 0.051 cm). The cranio-lateral processes were the shortest, and the caudo-ventral processes were the longest. The height of the keel was maximum at its apex.